HBR's 10 Must Reads on Technology and Strategy Collection - Porter, Michael E.; Christensen, Clayton M.; McGrath, Rita Gunther; Davenport, Thomas H. (La Vergne : Harvard Business Review Press, 2020)
Are analytics and technology a strategic part of your business' Artificial intelligence, platforms, algorithms, machine learning. Most business leaders know the value in advanced technologies. But how do you embed them into your business,and make them a key part of your strategy' HBR's 10 Must Reads Technology and Strategy Collection features innovative ideas to help you understand what new technologies offer, decide what business models are best for your business, and move forward with new innovations. Included in this seven-book set are: -HBR's 10 Must Reads on AI, Analytics, and the New Machine Age -HBR's 10 Must Reads on Business Model Innovation -HBR's 10 Must Reads on Platforms and Ecosystems -HBR's 10 Must Reads on Innovation -HBR's 10 Must Reads on Design Thinking -HBR's 10 Must Reads on Strategy -HBR's 10 Must Reads on Strategy, Vol. 2 The collection includes seventy articles selected by HBR's editors from renowned thought leaders including Clayton M. Christensen, W. Chan Kim, Renee Mauborgne, and Thomas H. Davenport, plus the indispensable article "Why Every Company Needs an Augmented Reality Strategy" by Michael E. Porter and James E. Heppelmann. With HBR's 10 Must Reads Technology and Strategy Collection, you can bridge the divide between your digital and strategic efforts, and ensure your business is on the cutting edge. HBR's 10 Must Reads paperback series is the definitive collection of books for new and experienced leaders alike. Leaders looking for the inspiration that big ideas provide, both to accelerate their own growth and that of their companies, should look no further. HBR's 10 Must Reads series focuses on the core topics that every ambitious manager needs to know: leadership, strategy, change, managing people, and managing yourself. Harvard Business Review has sorted through hundreds of articles and selected only the most essential reading on each topic. Each title includes timeless advice that will be relevant regardless of an ever-changi
Ch. 3: The Right Way to Lead Design Thinking -- Ch. 4: Design for Action -- Ch. 5: The Innovation Catalysts -- Ch. 6: Know Your Customers' ""Jobs to Be Done -- Ch. 7: Engineering Reverse Innovations -- Ch. 8: Strategies for Learning from Failure -- Ch. 9: How Indra Nooyi Turned Design Thinking into Strategy -- Ch. 10: Reclaim Your Creative Confidence -- About the Contributors -- Index -- Strategy -- Contents -- What is Strategy? -- The Five Competitive Forces That Shape Strategy -- Building Your Company's Vision -- Reinventing Your Business Model -- Blue Ocean Strategy
Description based upon print version of record.
The Secrets to Successful Strategy Execution.
Master record variable field(s) change: 050, 082, 650
Keywords: Technological innovations -- Economic aspects; BUSINESS & ECONOMICS / New Business Enterprises; Business; elektronické knihy; electronic books